EBUS-TBNA in diagnosis of pulmonary hamartoma: is it possible? - Wael Emam; Fatma Hafez; Nehad Osman (The Egyptian Journal of Bronchology)
Abstract Background Pulmonary hamartoma is an extremely rare benign neoplasm of the lungs. Patients usually present in the 4th and 5th decades of life and usually present as a hilar mass that needs to be biopsied to confirm the nature of the lesion. We report a case of pulmonary hamartoma that was diagnosed with EBUS-TBNA. Case presentation A 45-year-old female patient, non-smoker presented with dyspnea at moderate exertion. A CT scan showed a well-circumscribed left hilar mass. EBUS was planned and 3 passes EBUS-TBNA were taken and the final histopathological diagnosis was surprisingly pulmonary hamaroma. Conclusions EBUS-TBNA allows to locating of undiagnosed mediastinal lesions and performing a targeted needle aspiration, in a less invasive way, that can provide enough material for a certainty diagnosis in mediastinal hamartoma disease.